Bibliographic Organisation of Food Literature in the Commonwealth: Role of India - Sangameswaran, S. V.; Gopinath, M. V. (Journal of Information and Knowledge, 1980)
Presents data on Food Science and Technology literature emanating from Commonwealth countries. Highlights the characteristics of research done in Commonwealth countries, in terms of food supply and demand by the varying population, the number of on-going research projects, variety of literature output, and the secondary information services operating in the field. Discusses the variety of services provided by the Central Food Technological Research Institute as a National Information Centre in Food Science and Technology.